Genetic Tolerance to Rose Bengal Photodynamic Therapy and Antifungal Clinical Application for Onychomycosis. Issue 2 (12th September 2018) - Houang, Jessica; Perrone, Gabriel G.; Pedrinazzi, Christian; Longo, Leonardo; Mawad, Damia; Boughton, Philip C.; Ruys, Andrew J.; Lauto, Antonio
Abstract: Photodynamic therapy (PDT) with rose bengal has seen increasing use in clinical applications and has shown effective antifungal capacity in vitro. However, there is limited understanding of the effects of this emerging therapy at a genetic level. A rose bengal PDT screen using a green laser ( λ = 532 nm) on the entire non‐essential gene library of the model organism, Saccharomyces cerevisiae, and a subsequent pilot patient study ( n = 6 patients) in the treatment of onychomycosis caused by Trichophyton rubrum is reported. Of the 4800 yeast strains screened, 482 sensitive and 175 resistant strains are identified. The key biochemical pathways found to be affected included ergosterol biosynthesis, vacuolar acidification, and purine/S‐adenosyl‐l‐methionine biosynthesis. The implications of these findings inform the clinical application of an optimized rose bengal PDT protocol involving nail treatment with a rose bengal solution (140 µm ) and green light irradiation (fluence ≈763 J cm −2 ). All patients achieved complete cure within three to five treatment sessions in the absence of pain or other side effects. The outcome of the genetic screen may thus inform the development of more efficient clinical treatments using rose bengal PDT, as demonstrated in the successful treatment of onychomycosis. Abstract : A rose bengal photodynamic therapy (PDT) screen using green light of the entire non‐essential yeast gene library reveals the key affected biochemical pathways and cellular functions. These findings help to optimize the successful clinical application of rose bengal PDT for the treatment of toenail onychomycosis in a pilot study, with all patients achieving complete clearance.